1993
DOI: 10.1177/039139889301601004
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Changes following Parathyroidectomy

Abstract: Biochemical changes that had appeared after subtotal parathyroidectomy (PTx) in 26 patients with end-stage renal failure were observed. The volume of excised parathyroid glands was also measured. Serum calcium and inorganic phosphorus levels fell after PTx; only to rise in due course. Serum alkaline phosphatase levels rose after PTx, reaching a peak by the 14th post-operative day. These elevated levels returned to normal range at about three months after PTx. Strong correlation was noted among the degree of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…We found that, similar to previous reports, 7,13 preoperative ALP was an independent risk factor of very severe hypocalcemia in patients with SHPT, while ALP increment was not different between the two groups, in contrast to Chandran's finding. 17 We believe that ALP increment does not have time to change significantly in the short measurement period after TPTX used in our study, but it might show a stronger relationship with hypocalcemia over a longer time period. One of the strengths of the study is that we prefer to use TPTX in preference to other surgical strategies where possible, so that the bias from the surgery is as low as possible.…”
Section: Discussionmentioning
confidence: 66%
“…We found that, similar to previous reports, 7,13 preoperative ALP was an independent risk factor of very severe hypocalcemia in patients with SHPT, while ALP increment was not different between the two groups, in contrast to Chandran's finding. 17 We believe that ALP increment does not have time to change significantly in the short measurement period after TPTX used in our study, but it might show a stronger relationship with hypocalcemia over a longer time period. One of the strengths of the study is that we prefer to use TPTX in preference to other surgical strategies where possible, so that the bias from the surgery is as low as possible.…”
Section: Discussionmentioning
confidence: 66%
“…With primary hyperparathyroidism, variables predictive of postoperative hypocalcemia are adenoma volume, blood urea nitrogen, AlkP, and age [19]. With renal hyperparathyroidism, elevated bone turnover state is clearly associated with postoperative hypocalcemia [3][4][5][13][14][15][16][17][18]. PTH levels have been exploited as a screening tool to determine the type of renal osteodystrophy because of good correlation with bone histology [1,8].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our results, Chandran et al observed a strong correlation among the degree of postoperative hypocalcemia and transient postoperative increases in serum ALP, but not between absolute pre‐ and postoperative ALP levels in patients who underwent subtotal parathyroidectomy. 18 Their results suggest that not absolute ALP levels, but ALP increments after parathyroidectomy, are important to predict the degree of hypocalcemia. Although we did not examine the correlation between postoperative ALP increments and the degree of hypocalcemia, the difference may be partly due to the effect of PTH from the residual parathyroid glands on postoperative hypocalcemia in patients with subtotal parathyroidectomy.…”
Section: Discussionmentioning
confidence: 99%